(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Krupsky О., Kiba K. Interrelation between emotional competence and leadership as components of pedagogical activity. The article is devoted to a problem of interrelation of emotional intelligence and leadership, their influence on pedagogical activity, and also communication identification between emotional intelligence of teachers and pupils of averages and higher educational institutions.